Rhizopus stolonifer에 의한 산딸기 무름병 발생 - 권진혁(Jin-Hyeuk Kwon); 쩐티펑지(Tran Thi Phuong Chi) (Sigmulbyeong yeon'gu, 2008)
Rhizopus soft rot caused by Rhizopus stolonifer on June, 2008 occurred on Rubus crataegifolius Bunge in the box at Jinju City Wholesale Market of Agricultural Products at Gyeongnam province in Korea. The infected fruits were rapidly water-soaked, softened, black and eventually rotted. The symptoms occurred after infecting wounds at harvest time. The colony were white to light brown, formed much sporangiospores. The optimum temperature of the fungus on potato dextrose agar was $30^{°}C$. Sporangiophores were $12{\sim}25μm$ in width. Sporangia were globose or hemispheric, white at first and gradually to black, and $82{\sim}195μm$ in size. Columella were hemispheric, and $70{\sim}92μm$ in size. Sporangiospores were irregular round or oval, brownishblack and $9{\sim}21{×}7{\sim}8μm$ in size. On the basis of symptom, mycological characteristics and pathogenicity of the fungus, the causal fungus was identified as Rhizopus stolonifer. This is the first report of Rhizopus soft rot by R. stolonifer on R. crataegifolius in Korea. 2008년 6월 상순 경남 진주시 농산물도매시장에 유통 판매중인 산딸기에서 이상증상이 발생하였다. 병징은 과실표면에 상처 또는 짓물러진 과실부분이 수침상으로 물러지면서 빠르게 부패되었다. 균총은 처음 흰색에서 연한 회색으로 되고 검은색의 포자낭을 많이 형성하였으며 균사생육 적온은 $30^{°}C$이었다. 포자낭경은 처음 흰색에서 연한 회색을 나타내며 폭은 $12{\sim}25μm$이었다. 포자낭은 검은색으로 구형 또는 반구형이며 크기는 $82{\sim}195μm$이었다. 주축은 반구형이며 크기는 $70{\sim}92μm$이었다. 포자낭 포자는 담갈색으로 단포이며 구형 또는 타원형이고 불규칙한 것도 있으며 크기는 $9{\sim}21{×}7{\sim}8μm$이었다. 따라서 산딸기 과실에 발생한 병징과 병원균의 균학적 특징 및 병원성을 검정한 결과, 본 병해를 Rhizopus stolonifer에 의한 산딸기 무름병으로 명명할 것을 제안한다.